THE EFFECTIVENESS OF EMOTIONAL INTELLIGENCE TRAINING TO REDUCE AN INTENTION OF BULLYING BEHAVIOUR - Annisa Warastri (LP2M Universitas Sarjanawiyata Tamansiswa, 2018)
Bullying happens when an individu or a group of people harassed or threatened someone elseâ€™s security and well-being (health) both in physicall or psychological, threatened the reputation or social acceptance of someone and done repeatedly and continously (Kustanti, 2015).Some of Bullying behaviour that researchers found including, mocking, disgracing, calling out a name and sticking out tongue. Researchers also found some cases of client where the clients (students) felt that they been bullied by their friends by being ignored and ostracized by its environment. One of the factors that bullying happens are the characteristic of an individu.In this study, the researcher will held a training about emotional intelligence for some individuals that had a tendency to practice bullying.Subject in this research including 30 individuals that will be selected randomly and had a tendency to show an intention to have a bullying behaviour. Afterwards, the subject will be given an emotional intelligence training for at most 5 session.The result of this study shows that there is an intention reduction of bullying behaviour owned by the subject of this study after the session of emotional intelligence training held, and it shows in the decrease of the posttest score of the subject compare to the pretest score, 93 to 74 respectively. By the changing of this score it is indicated that the emotional intelligence training effectively reduce the bullying behaviour in the subject of this study.Â Keyword: Bullying, Emotional Intelligence, Student.